My journey through the history of development economics - Erik Thorbecke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper is essentially autobiographical and describes Erik Thorbecke's journey through the history of development economics between the 1950s and the present. The paper consists of four parts. First, an introduction reviews briefly his professional career as a development economist and his research interactions with major contributors to the discipline. The next three parts review critically his contributions to research on and training in, respectively, (i) the ongoing process of African development; (ii) income distribution, inequality, and poverty; and (iii) economic structure, interdependence, and quantitative development analysis.
Keywords: B31; B40; C54; O10; 330; development doctrine; inequality; poverty; Africa; economic structure; Erik Thorbecke